THE VISUAL AND SPATIAL INFLUENCE OF TEMPLES UPON SOUTH INDIAN TEMPLE TOWNS - Satyavarapu, Gowthami (2023)
Temple cities of south India have achieved the highest social, cultural, and economic ideals through many centuries, representing a unique genre of built fabric and functioning as independent social units. Over time, the concept of a south Indian temple city has evolved from simple settlements into a complex theory that incorporates a huge deal of experience and experimentation. In the context of South Indian temple cities, the temple complex is not limited to the central core, but encompasses the whole settlement, which is recognized for its ability to adapt to urban change and continued habitation. In South Indian temple cities, the built environment is arranged, proportioned, and designed to reflect the physical, cultural, and functional setting. Throughout the ages, the temple cities of South India have been shaped by numerous cultural and political influences that left an indelible mark on their visual fabric. The purpose of this study is to examine how temples and temple towns have interacted over time, examining the relationship between the development of temple towns in South India. Throughout the course of the research, temples are examined in terms of how they shape the architectural styles and design elements of the surrounding urban fabric, and how they are oriented and situated within the urban context to create spatial and visual hierarchies, which affect the overall layout and design of the city. Moreover, the study explains how temple festivals and rituals, such as the Ratha Yatra, shape the social and cultural life of South Indian temple towns and how they are manifested in urban settings. In addition, the study examines how urbanization and development pressures affect the historic fabric of South Indian temple towns and how these cities can preserve their unique cultural and religious heritages. In traditional South Indian temple towns, the urban fabric reflects the community's cultural needs and aspirations and is based on a variety of architectural and planning frameworks. In these towns, the built environment is inextricably linked to religious and cultural practices based on the metaphysical interpretation of space. This study explores the basic norms that govern the structure and function of Indian temple towns and analyzes how temples interact with the surrounding urban fabric. Temples are often the focal points of these towns, and their architectural styles and design elements influence the surrounding urban fabric. This study analyzes three temple cities in South India on the basis of their social, architectural, and cultural continuities and changes. Combined with the socio-cultural attributes of these spaces, interconnections between people have caused a considerable spatial configuration. In addition to implementing both quantitative and qualitative approaches, the research utilizes combinational research strategies such as logical reasoning, comparative simulation and descriptive-analysis to examine the South Indian temple towns. The study also includes questionniers, field studies, documentation, questionnaires and desk research. As part of this study, three primary components are considered for analysing the environmental image: Gopuram represents identity, Ratha Yatra represents structure, and temple represents meaning. Our main goal is to gain insight into how these three components contribute both to the form and function of temple towns in South India. In this study, the architectural styles and style elements of temples in South India are analyzed and their influence on the surrounding urban fabric is discussed in relation to the historical development of South Indian temple towns. A study of how temples are positioned and oriented within the urban environment in order to establish visual and spatial hierarchies, assessing the social and cultural impact of temple festivals and rituals in South Indian temple towns, and identifying the challenges and opportunities for preserving the historic fabric of South Indian temple towns despite the pressures of urbanization and development. The visual influence of southern Indian temples on the built environment has been examined using a regression model, and a number of samples of visual heritage, as well as direct observations and documentation, have been collected. Through the analysis of the composition of south Indian temple cities, the findings of this research will contribute to the preservation and enhancement of India's rich cultural and architectural heritage.